Social Deixis and Power Relations in Habib Ja’far’s YouTube Preaching - Abdullah (Faculty of Adab and Humanities, Syarif Hidayatullah State Islamic University (UIN) Jakarta, 2025)
This study examines how personal and social deixis function as pragmatic strategies in the YouTube sermons of Habib Ja’far, a prominent figure in popularizing contemporary Islamic discourse. Adopting a qualitative sociopragmatic approach, the research analyzes twenty-two video excerpts across multiple YouTube channels—Jeda Nulis, VINDES, Metro TV, and Close the Door—to investigate how linguistic choices mediate persona construction, audience engagement, and digital religious authority. The analysis integrates Levinson’s (1983) framework of deixis, Goffman’s (1981) concept of footing, Brown and Levinson’s (1987) politeness theory, and Bell’s (1984) audience design model, contextualized within Campbell’s (2012) notion of performative digital authority. Findings reveal four dominant patterns: (1) personal deixis (saya, aku, gua, kita) as a tool for negotiating persona and inclusivity; (2) social deixis (Mbah, Bang Haji, Sahabat saya yang non-Muslim) as a resource for structuring hierarchy and solidarity; (3) intertextual deixis linking modern egalitarian speech with prophetic authority; and (4) cross-format deixis variation reflecting adaptive pragmatics across genres and platforms. The study concludes that Habib Ja’far’s deixis exemplifies a hybrid, performative, and participatory model of religious authority, where linguistic adaptability and relational sincerity underpin the effectiveness of Islamic communication in the digital public sphere.